Fatigue as a limitation to performance - Ball, D.; Maughan, R. J. (Experimental Physiology, 2021)
Scientific interest in the nature and causes of exercise-induced fatigue developed through the 19th century, culminating in the publication in 1891 of a monograph on the subject by Angelo Mosso (Mosso, 1891). Mosso had developed an ergographic method to quantify fatigue of the muscles of the middle finger in response to voluntary or electrically evoked contractions. Other methodological advances led to a focus on different exercise models and on specific aspects of the fatigue process. August Krogh developed a reliable cycle ergometer that has remained the standard laboratory exercise model and also an accurate method for the analysis of expired air (Krogh, 1913). The introduction of the needle biopsy method for obtaining samples of human muscle, by Jonas Bergstrom in the 1960s, shifted the focus to the role of substrate depletion and metabolite accumulation in the active muscles (Bergstrom, 1962). A working definition of fatigue was proposed by Richard Edwards at the 1981 Ciba Foundation symposium: `fatigue is a failure to maintain the required or expected work output` (Edwards, 1981). The symposium covered aspects of fatigue from the perspectives of the central and peripheral neuromuscular system. Various international symposia dedicated to the topic of fatigue were held in the 1980s and 1990s, for example, the 1994 International Symposium on Neural and Neuromuscular Aspects of Muscle Fatigue (Gandevia et al., 1994). As part of its 2019 annual meeting, hosted in Aberdeen, The Physiological Society organised five satellite symposia on the day prior to the main conference. The theme of one of these satellite symposia was `Fatigue as a limitation to performance`, and it was based upon three separate but inter-related sessions that focused on the neuromuscular system and fatigue, the cardiovascular system and fatigue, and finally, muscle metabolism and fatigue.